Covariant Impulse Approximation for the study of the internal structure of composite particles. - Maurizio De Sanctis; Mario A. Acero; Diego A. Milanés; Carlos E. Sandoval (Momento, 2004)
We present a brief review on the Impulse Approximation method to study processed of scattering off composite particles. We first construct the model in a non-relativistic fashion that enables us to extend the model to a covariant Impulse Approximation, which is needed for the study of high momentum transfer processes.